Factors associated with smoking cessation in Brazil - Cesar Augusto Oviedo Tejada; Fernanda Ewerling; Anderson Moreira Aristides dos Santos; Andréa Dâmaso Bertoldi; Ana Maria Menezes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
Tobacco has been identified as the drug with the highest addiction rate and the leading cause of avoidable deaths. The current study thus aimed to identify the determinants of smoking cessation in a Brazilian population sample based on data from the National Household Sample Survey for 2008. The study analyzed socioeconomic, residential, and health-related data as well as individual habits. Data analysis used Poisson regression. The following factors were associated with smoking cessation: age 45 years or older, higher income, medical consultation in the previous 12 months, private health plan, physical exercise, believing that smoking is bad for one's health and that cigarette smoke is harmful to passive smokers, and Internet access in the household. Subjects with heart conditions, diabetes, and cancer were also more prone to quit smoking.